Nonlinear finite element analysis of unbonded prestressed concrete beams subjected to short-term loading - Alves, Juliana Cunha (2019)
Prestressed concrete with unbonded tendons is an excellent structural solution for beams and slabs, allowing the design of slender elements with long spans. However, the consideration of the unbonded tendon in the structural analysis is complex, requiring the development and implementation of adequate methods. This work presents a finite element model formulation for material and geometric nonlinear analysis of unbonded prestressed beams. The Euler-Bernoulli nonlinear plane frame element formulation for large displacements and moderate rotations is used to model the reinforced concrete beam. The tendon is modeled as a single polygonal element with a variable number of straight segments. The tendon element allows the consideration of material and geometric nonlinearities. The formulation was successfully implemented and the obtained results were in good agreement with experimental data for beams with external and internal unbonded tendons. The presented formulation was applied to assess the influence of the geometric nonlinearity on the structural behavior of presstressed beams with unbonded tendons. The results showed that the geometric linear analysis overestimates the beam capacity.